Strengthening Risk Literacy through Digital-Based Insurance Learning in Indonesia - Dyah Prita Anggraini Anggraini; Nurmalina Marpaung (Indonesian Journal Economic Review (IJER), 2026)
The study examines the effectiveness of digital insurance education in improving risk literacy in Indonesia. Risk literacy is an essential part of financial literacy because it enables individuals to understand uncertainty, assess potential losses, and make informed financial decisions. Public understanding of risk and insurance, however, remains relatively low, which calls for more innovative educational strategies. A quantitative approach was applied through a quasi-experimental design using pre-test and post-test measures. Data were collected from 120 participants who completed digital learning modules consisting of interactive videos, simulations, and case-based materials on risk and insurance. Paired-sample t-tests and regression analysis were used to assess the effect of the intervention. The findings indicate a significant increase in participants’ risk literacy, as reflected in higher post-test scores than pre-test scores. Engagement in digital learning also showed a positive and significant effect on learning outcomes. The results suggest that digital learning can serve as an effective and scalable method for improving public understanding of risk and insurance. The study also provides a basis for an integrated framework linking digital learning, insurance education, and risk literacy. From a practical perspective, the findings may guide policymakers and educators in designing accessible and technology-driven educational programs to improve financial literacy and risk awareness in Indonesia.